Features of nanoparticle composite-enhanced CO2 foam-flooding systems for low-permeability reservoirs - Liu, Yong; Zhao, Fajun; Niu, Ruixia; Cao, Sheng; Liu, Lei; Song, Yarui (Frontiers in Energy Research, 2023)
This study examined an enhanced foam-flooding system incorporating nanoparticles and polymers under geological conditions of a reservoir of the Shu 16 block in the Yushulin oilfield. The system is mainly comprised of an anionic foaming agent (CQS-1) and a nonionic surfactant (FH-1). We screened 17 foams by evaluating their foaming volumes and foam half-lives using a Waring-blender and dynamic foam analysis methods, and nanoparticles were selected after examining each foam’s concentration, the ratio of the main agent to the auxiliary agent, and the dosage of the foam stabilizer. Then, we analyzed the selected system’s microstructure and rheological properties, including the adaptability of the reservoir to its temperature resistance, salt tolerance, and adsorption resistance. As a result, this study supports the field application of CO2 foam flooding.